Evaluation of using Google Classroom as a Tool for Asynchronous E-learning at Sebha University - Alssager , Mansour; Nasir , Ibrahim (Journal of Pure & Applied Sciences, 2021)
Recently, technology is anywhere and everywhere, and education systems are affected by technology at a rapid pace, that increasingly advance the career of students as well as the teachers. The current worldwide trend is to learn online since the coronavirus pandemic outbreak, whereby E-learning is not optional rather it is mandatory. This study has been carried out to assess the effectiveness of E-Learning facility mainly Google Classroom at Sebha University. Five aspects of Google Classroom usage are measured including the perceived ease of use, the perceived usefulness, Communication and interaction, benefit, student satisfaction. A set of questionnaires have been distributed to a sample of 94 students in different bachelor and master subjects. The results shows that all the ratio of the five measured aspects where all above averages, which prove that majority of the students satisfy with the Google Classroom’s tool that were introduced in the class.